O Fazer Teológico como Hermenêutica-Transdisciplinar: A Teologia desafiada pelo Pensamento Complexo de Edgar Morin - Souza, Sandro Alves Martiniano de (2012)
The research seeks to identify ways in which the relational dynamics that must exist between the knowledge/theological and other forms of knowledge in contemporary society, based on the French philosopher Edgar Morin in his theoretical framework titled Complex Thinking. From this perspective, the research outline for a hermeneutic or a complex transdisciplinary hermeneutics. This concept (transdisciplinary hermeneutics / hermeneutics in complexity) is not a deductive system, but an open system, operated by an open reason (rationality) that seeks to interpret contemporary reality by observing the tradition. Also creatively interprets the tradition as a response to contemporary emerging amid a complex reality. From this concept note is also the dynamic relationships of knowledge of that time, and this, not just looking through the lens of interdisciplinarity, but going beyond, becoming a transdisciplinary knowledge. Christian theology is still love-biblical tradition, never become a complete and finished system of theological knowledge. Past and present complete and only shed light for the future. For this, the Christian theological tradition, the Bible is reflective foundation sand axioms, from which we can reflect on all the topics that will impose knowledge (complexity in reality) as thematization.